Certifica Minas Café: a new paradigm of the state government in environmental protection? - Castro, Claudio Vieira; Salgado, Eduardo Gomes; Beijo, Luiz Alberto (Coffee Science - ISSN 1984-3909, 2017)
The Certifica Minas Café program is an initiative of the government of the State of Minas Gerais for the certification of coffee farms. It is the only coffee certification program promoted by the Government. This research was intended to address one of the program's challenges: to deal with nonconformities found in audits and that may be associated with legal obligations. After all, the CMC's auditors also have inspection duties on the use of pesticides. The survey had access to 570 audit reports performed by the program in the year 2015, and randomly selected a sample of 230 properties. From the reports were extracted data on six certification requirements, associated with pesticides. Interviews were conducted with the program managers and examined the certification procedures and forms. As it was evidenced that there are situations of nonconformities associated with legal obligations, there may be conflict in the performance of the auditors, who are also fiscals. However, when comparing the nonconformities of certified properties with surveys that approached non-certified properties, it was observed that certification improves compliance with standards. By choosing not to impose sanctions, the CMC has become an instrument of environmental education. In this sense, the hypothesis is that the public certifications of agricultural products can be a new paradigm of the state action in the protection of the environment.